PERLINDUNGAN PEREMPUAN DAN ANAK KORBAN TRAFFICKING DI KABUPATEN KAPUAS HULU - Siti Hariti Sastriyani (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
This study aims to determine the cases of trafficking that occur in Kapuas Hulu. Some prevention efforts, a form of protection of victims and develop a model of protection of victims. Methods of data analysis performed using qualitative descriptive analysis with a sample of Sub Badau traffic being trafficked in Indonesia-Malaysia border. The results showed that some types of work done by the women and the children victims of trafficking are workers in places of entertainment, plantation workers, and etc. As for some of the factors that influence the occurrence of trafficking is the opening of the Postal Cross Border (PLB) Entikong Sanggau district. One of the prevention efforts that can be done by the Kapuas Hulu regency government is makes education and health as a priority program.